2020
DOI: 10.1104/pp.19.01399
|View full text |Cite
|
Sign up to set email alerts
|

The Four Arabidopsis Choline/Ethanolamine Kinase Isozymes Play Distinct Roles in Metabolism and Development

Abstract: Phosphatidylcholine and phosphatidylethanolamine are 2 major phospholipid classes in eukaryotes. Each biosynthesis pathway starts with the phosphorylation of choline (Cho) or ethanolamine (Etn) catalyzed by either choline or ethanolamine kinase (CEK). Arabidopsis contains 4 CEK isoforms but their isozyme-specific roles in metabolism and development are poorly described. Here, we showed that these 4 CEKs have distinct substrate specificities in vitro. While CEK1 and CEK2 showed substrate preference for choline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In conclusion, the specific effect of coumarin on Ca 2+ reabsorption, which was not observed for K + , could represent a crucial point in its inhibitory action. Phosphocoline is an intermediate in phospholipids’ biosynthesis that is related to membrane biosynthesis, a crucial event in seed germination [ 35 , 36 ]. In the present study, phosphocholine, with production that is strictly dependent on ATP, was significantly lower after 24 h of treatments (in agreement with the lower ATP level observed) but was restored to the control level after 48 h. These data strongly support the hypothesis that during the first 24 h of treatment, coumarin could delay membrane synthesis and organisation.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the specific effect of coumarin on Ca 2+ reabsorption, which was not observed for K + , could represent a crucial point in its inhibitory action. Phosphocoline is an intermediate in phospholipids’ biosynthesis that is related to membrane biosynthesis, a crucial event in seed germination [ 35 , 36 ]. In the present study, phosphocholine, with production that is strictly dependent on ATP, was significantly lower after 24 h of treatments (in agreement with the lower ATP level observed) but was restored to the control level after 48 h. These data strongly support the hypothesis that during the first 24 h of treatment, coumarin could delay membrane synthesis and organisation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with T‐DNA knockout lines and overexpression lines revealed that only CEK4 functions as an Etn kinase (Lin et al. , 2020). In contrast to PMT1, which is feedback inhibited by PCho (BeGora et al.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana, four homologous CEKs were identified (Lin , 2015). Recent studies with T-DNA knockout lines and overexpression lines revealed that only CEK4 functions as an Etn kinase (Lin et al, 2020). In contrast to PMT1, which is feedback inhibited by PCho (BeGora et al, 2010), it is not known whether CEK4 is under metabolic control, for example, inhibited by its product, PEtn.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, phosphatidylethanolamine (PE) levels are unaffected in ChoKβ KO mice, a result which suggests that PE homeostasis is fully maintained when the ChoKα protein is intact [9]. Again, in Arabidopsis, substrate specificity for Cho and Etn are distinct for the four CEK enzymes [14] and resembles the situation described in mammalian cells [15].…”
Section: The Chok Family In Humansmentioning
confidence: 98%
“…In humans, mutations in the CHKB gene lead to similar pathology [13]. Finally, in Arabidopsis, there are four Choline-Ethanolamine Kinase (CEK) genes related to choline (Cho) and ethanolamine (Etn) phosphorylation, with different roles in metabolism and development [14].…”
Section: The Chok Family In Humansmentioning
confidence: 99%